A toxicokinetic study of specifically acting and reactive organic chemicals for the prediction of internal effect concentrations in Scenedesmus vacuolatus. (1st December 2014) - Vogs, Carolina; Kühnert, Agnes; Hug, Christine; Küster, Eberhard; Altenburger, Rolf
Abstract The toxic potency of chemicals is determined by using the internal effect concentration by accounting for differences in toxicokinetic processes and mechanisms of toxic action. The present study examines toxicokinetics of specifically acting and reactive chemicals in the green algae Scenedesmus vacuolatus by using an indirect method. Concentration depletion in the exposure medium was measured for chemicals of lower (log KOW < 3: isoproturon, metazachlor, paraquat) and moderate (log KOW 4‐5: irgarol, triclosan, N‐phenyl‐2‐naphthylamine) hydrophobicity at 7 to 8 time points over 240 min or 360 min. Uptake and overall elimination rates were estimated by fitting a toxicokinetic model to the observed concentration depletions. The equilibrium of exposure concentrations was reached within minutes to hours or was even not observed within the exposure time. The kinetics of bioconcentration cannot be explained by the chemical's hydrophobicity only, but influential factors such as ionization of chemicals, the ion trapping mechanism, or the potential susceptibility for biotransformation are discussed. Internal effect concentrations associated with 50% inhibition of S. vacuolatus reproduction were predicted by linking the bioconcentration kinetics to the effect concentrations and ranged from 0.0480 mmol/kg wet weight to 7.61 mmol/kg wet weight for specifically acting and reactive chemicals. Knowing the time‐course of the internal effect concentration may promote an understanding of toxicity processes such as delayed toxicity, carry‐over toxicity, or mixture toxicity in future studies. Environ Toxicol Chem 2015;34:100–111. © 2014 SETAC